2020
DOI: 10.1016/j.jhin.2019.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-outbreak of Mycobacterium paragordonae in a hospital: possible role of the aerator/rectifier connected to the faucet of the water supply system

Abstract: Background: Pseudo-outbreaks of non-tuberculous mycobacteria (NTM) in association with the water supply system in hospitals have been previously reported. We found that the frequency of NTM isolation in clinical samples increased after the reconstruction and renovation of a hospital in Japan in 2014. Aim: To analyse NTM, their possible relationship with the hospital water supply system, and outcomes of preventive measures. Methods: Environmental samples obtained from the water supply in hospital wards were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Fixtures such as faucets, aerators, fountains (bubblers), thermostatic mixing valves, showerheads, and shower hoses can be relatively easily removed, cleaned, and/or discarded. Pathogen growth and heavy metal accumulation (e.g., particles of copper, iron, lead) have been associated with these plumbing components (Bédard et al, 2015; Cohen et al, 2017; Huang & Lin, 2007; Kappstein, Grundmann, Hauer, & Niemeyer, 2000; Proctor, Reimann, Vriens, & Hammes, 2018; Shaw et al, 2018; Sydnor et al, 2012; Takajo et al, 2019; Verweij et al, 1998; Wang, Chen, Lin, Chang, & Chen, 2009; Weber, Rutala, Blanchet, Jordan, & Gergen, 1999; Whiley, Giglio, & Bentham, 2015). Thermostatic mixing valves, used in showers and faucets to mix hot and cold water to prevent scalding, have been identified as particularly problematic for the growth of Legionella (Niedeveld, Pet, & Meenhorst, 1986; van der Lugt et al, 2017; Van Hoof, Hornstra, Van Der Blom, Nuijten, & Van Der Wielen, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Fixtures such as faucets, aerators, fountains (bubblers), thermostatic mixing valves, showerheads, and shower hoses can be relatively easily removed, cleaned, and/or discarded. Pathogen growth and heavy metal accumulation (e.g., particles of copper, iron, lead) have been associated with these plumbing components (Bédard et al, 2015; Cohen et al, 2017; Huang & Lin, 2007; Kappstein, Grundmann, Hauer, & Niemeyer, 2000; Proctor, Reimann, Vriens, & Hammes, 2018; Shaw et al, 2018; Sydnor et al, 2012; Takajo et al, 2019; Verweij et al, 1998; Wang, Chen, Lin, Chang, & Chen, 2009; Weber, Rutala, Blanchet, Jordan, & Gergen, 1999; Whiley, Giglio, & Bentham, 2015). Thermostatic mixing valves, used in showers and faucets to mix hot and cold water to prevent scalding, have been identified as particularly problematic for the growth of Legionella (Niedeveld, Pet, & Meenhorst, 1986; van der Lugt et al, 2017; Van Hoof, Hornstra, Van Der Blom, Nuijten, & Van Der Wielen, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Fixtures such as faucets, aerators, fountains (bubblers), thermostatic mixing valves, showerheads, and shower hoses can be relatively easily removed, cleaned, and/or discarded. Pathogen growth and heavy metal accumulation (e.g., particles of copper, iron, lead) have been associated with these plumbing components Cohen et al, 2017;Huang & Lin, 2007;Kappstein, Grundmann, Hauer, & Niemeyer, 2000;Proctor, Reimann, Vriens, & Hammes, 2018;Shaw et al, 2018;Sydnor et al, 2012;Takajo et al, 2019;Verweij et al, 1998;Wang, Chen, Lin, Chang, & Chen, 2009;Weber, Rutala, Blanchet, Jordan, & Gergen, 1999;Whiley, Giglio, & Bentham, 2015). Thermostatic mixing valves, used in showers and faucets to mix hot and cold water to prevent scalding, have been identified as particularly problematic for the growth of Legionella (Niedeveld, Pet, & Meenhorst, 1986;van der Lugt et al, 2017;Van Hoof, Hornstra, Van Der Blom, Nuijten, & Van Der Wielen, 2014).…”
Section: Considerations For Flushing Plansmentioning
confidence: 99%
“…[ 8 ], Takajo et al . [ 9 ], and Moradi et al . [ 17 ] showed that MPG could also be isolated at an incubation temperature of 37°C.…”
Section: Discussionmentioning
confidence: 99%
“…Mycobacterium paragordonae (MPG) was first isolated from the lungs of a patient in Korea in 2014 [ 7 ]. As with MG, MPG is also a slow-growing, pigmented (orange) bacterium that is widely found in the environment, such as soil and water, and is often considered a contaminating bacterium that can be recovered from freshwater, pipelines, and laboratory faucets [ 8 , 9 ]. The DNA–DNA affinity comparison between MPG and the MG ATCC 14470 T standard strain was only 46.52%, which met the definition of a new species [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation